AKIBAT HUKUM TERHADAP RUNTUHNYA JEMBATAN KUTAI KARTANEGARA DITINJAU DARI UNDANG - UNDANG NOMOR 38 TAHUN 2004 TENTANG JALAN - Almahsuf Almahsuf (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
Abstract The road is a pedestrian transportation infrastructure, vehicles, cars and so on that connects between villages, cities, provinces and countries. Besides, it is a bridge between the two regions is the link between villages, cities, provinces and countries, which dipisahakan by creeks or ravines to be able to perform activities of pedestrian or driving.The law that occurred due to the collapse of the bridge Kutai the terms of the Act - Act No. 38 of 2004 on the road, which is dubbed the Golden Gate Bridge Indonesia collapsed during repair and maintenance. The incident has claimed many victims died and injuries - injuries, investigations carried out by the police and experts which have contained findings that the process of implementation of the program of repair and maintenance bridge access road to the bridge was not closed completely.The purpose of writing this scientific work that we know the cause and effect arising in the implementation of development, setting, Implementation, and setting the path to the bridge aquatic mammal which will be incurred as a result - and the legal consequences of violations.The spotlight on the issue is a government agency, police and other relevant parties such as road construction contractors, because there is no implementation of the Act - Act Road.From the research it was concluded that any development activity, regulation, implementation, and setting the path, should use the term two rabbits that communication and coordination between Government Agencies, Police, Community, and the parties concerned, so that the system formulation and implementation can be realized according to plan and to get good results and efficient.